Editorial - Smyrnova-Trybulska, Eugenia (International Journal of Research in E-learning, 2023)
The Editorial Board of International Journal of Research in E-learning (IJREL) is privileged to present a new volume 9(1) 2023. The content of the current issue was divided into three chapters. The first is devoted to Research on Distance, Online and Blended Learning in particular in the COVID-19 time. The second contains articles concerned with Innovative Methods and Technology in Education. The third concerns Theoretical, Methodological and Practical Aspects and Psychological Determinants of ICT and E-Learning in Education.